Effects of burning rice straw residue on-field on soil organic carbon pools: Environment-friendly approach from a conventional rice paddy in central Viet Nam. (May 2022) - Toan, Nguyen-Sy; Hanh, Do Hong; Dong Phuong, Nguyen Thi; Thuy, Phan Thi; Dong, Pham Duy; Gia, Nguyen Thanh; Tam, Le Duc; Thu, Tran Thi Ngoc; Thanh, Do Thi Van; Khoo, Kuan Shiong; Show, Pau Loke
Abstract: Rice straw residue management is still facing many problems worldwide. This study used two environmentally friendly methods to investigate the effects of rice straw burning activity on water-extracted carbohydrate content in long-term paddy soil. Soil samples were collected at a depth within 0–15 cm at the paddy field before and after burning rice straw (pre-burning and post-burning), then extracted by distilled water at the ratio of 1:10 (soil: water) for measuring hot water (at 80 °C) and water extracted carbohydrate (at 25 °C) (HECH and WECH). The results showed that burning rice straw did not alter soil organic carbon (SOC); however, soil pH increased approximately 8.3%. Meanwhile, WECH and HECH ranged from 233 to 630 mg kg −1, with the highest HECH in Pre-burning treatment, while the lowest amount addressed WECH of Post-burning treatment. Extracted carbohydrate decreased after burning rice straw compared to Pre-burning soil. On the other hand, hot water increased 39–58% of carbohydrates compared to water extraction. We conclude that burning rice straw did not affect SOC but tends to reduce their labile carbon pools, and the heating process likely degrade part of SOC when extracted at high temperatures. Graphical abstract: Image 1 Highlights: Burning rice straw residue did not alter soil organic carbon storage. Burning rice straw declines soil labile carbon pool. Burning rice straw residue increased soil pH. Burning rice straw residue enhance soil degradability.